Serotonin- and Dopamine-Related Gene Expression in db/db Mice Islets and in MIN6 β-Cells Treated with Palmitate and Oleate. (5th June 2016) - Cataldo, L. R.; Mizgier, M. L.; Busso, D.; Olmos, P.; Galgani, J. E.; Valenzuela, R.; Mezzano, D.; Aranda, E.; Cortés, V. A.; Santos, J. L.
Abstract : High circulating nonesterified fatty acids (NEFAs) concentration, often reported in diabetes, leads to impaired glucose-stimulated insulin secretion (GSIS) through not yet well-defined mechanisms. Serotonin and dopamine might contribute to NEFA-dependent β -cell dysfunction, since extracellular signal of these monoamines decreases GSIS. Moreover, palmitate-treated β -cells may enhance the expression of the serotonin receptor Htr2c, affecting insulin secretion. Additionally, the expression of monoamine-oxidase type B (Maob) seems to be lower in islets from humans and mice with diabetes compared to nondiabetic islets, which may lead to increased monoamine concentrations. We assessed the expression of serotonin- and dopamine-related genes in islets from db/db and wild-type (WT) mice. In addition, the effect of palmitate and oleate on the expression of such genes, 5HT content, and GSIS in MIN6 β -cell was determined. Lower Maob expression was found in islets from db/db versus WT mice and in MIN6 β -cells in response to palmitate and oleate treatment compared to vehicle. Reduced 5HT content and impaired GSIS in response to palmitate (−25%;p < 0.0001 ) and oleate (−43%;p < 0.0001 ) were detected in MIN6 β -cells. In conclusion, known defects of GSIS in islets from db/db mice and MIN6 β -cells treated with NEFAs are accompanied by reduced Maob expression and reduced 5HT content.